2009
DOI: 10.1016/j.str.2008.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Biological Function of the RNA Pyrophosphohydrolase BdRppH from Bdellovibrio bacteriovorus

Abstract: SUMMARY Until recently, the mechanism of mRNA decay in bacteria was thought to be different from that of eukaryotes. This paradigm changed with the discovery that RppH (ORF176/NudH/YgdP), an Escherichia coli enzyme that belongs to the Nudix superfamily, is an RNA resolution pyrophosphohydrolase that initiates mRNA decay by cleaving pyrophosphate from the 5′-triphosphate. Here we report the 1.9 Å structure of the Nudix hydrolase BdRppH from Bdellovibrio bacteriovorus, a bacterium that feeds on other Gram-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 50 publications
2
43
1
Order By: Relevance
“…A 43-nucleotide RNA (5Ј-GGAAUCUCUCUCUCUCUCUAUGCUCUCUCUCUCUCUCUC UCUC-3Ј) was transcribed and purified as previously described (1,23). To prepare the 5Ј-labeled substrate, phosphates on the 5Ј end were removed by Antarctic phosphatase (New England BioLabs) according to the manufacturer's instructions and rephosphorylated with [␥- To prepare the 3Ј-labeled RNA substrate, phosphates were removed from the 5Ј end with Antarctic phosphatase and the RNA was labeled using T4 RNA ligase (New England BioLabs) and [5Ј- 4C) and quenched with 95% formamide, 25 mM EDTA, 0.02% bromophenol blue, and 0.02% cyanol blue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 43-nucleotide RNA (5Ј-GGAAUCUCUCUCUCUCUCUAUGCUCUCUCUCUCUCUCUC UCUC-3Ј) was transcribed and purified as previously described (1,23). To prepare the 5Ј-labeled substrate, phosphates on the 5Ј end were removed by Antarctic phosphatase (New England BioLabs) according to the manufacturer's instructions and rephosphorylated with [␥- To prepare the 3Ј-labeled RNA substrate, phosphates were removed from the 5Ј end with Antarctic phosphatase and the RNA was labeled using T4 RNA ligase (New England BioLabs) and [5Ј- 4C) and quenched with 95% formamide, 25 mM EDTA, 0.02% bromophenol blue, and 0.02% cyanol blue.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to helping control the concentrations of crucial metabolites (e.g., ADP-ribose [12,19], UDP-glucose [46], and coenzyme A [4]), members of the superfamily also play key roles in biosynthetic pathways (e.g., folate biosynthesis [13]). It has been shown that some members of the Nudix family, i.e., Schizosaccharomyces pombe Dcp2 (31) and Escherichia coli and Bdellovibrio bacteriovorax RppH (7,23), may also play a role in RNA degradation by decapping mRNA.…”
mentioning
confidence: 99%
“…This family of enzymes has a characteristic fold consisting of two β sheets flanked by three α helices. Whereas E. coli RppH (EcRppH) and Bdellovibrio bacteriovorus RppH (BdRppH) catalyze the conversion of RNA 5′ triphosphate to 5′ monophosphate in a single step (i.e., with the release of pyrophosphate) (3,12), the B. subtilis enzyme performs this reaction in two steps, releasing two phosphate ions (4). Intrigued by this difference and conscious of the importance of B. subtilis as an alternative biological model for bacterial mRNA decay, we resolved the crystal structure of the B. subtilis RppH (BsRppH) enzyme in its free form, as well as that bound to GTP and a 5′-triphosphorylated dinucleotide RNA.…”
mentioning
confidence: 99%
“…The Nudix motif (23 residues from Gly-38 i.e. the MutT signature (GX 5 EX 7 REUXEEXGU), adopts the characteristic strand-loop-helix-loop (SLHL) structure formed by ␤-3Ј, L-B, ␣-1, and L-C (39,40). The crystal of the apo form contains two protein molecules per asymmetric unit, and they are very similar to each other with root mean square deviation (r.m.s.d.)…”
Section: Resultsmentioning
confidence: 99%